Analysis of cataract-regulated genes using chemical DNA damage induction in a rat ex vivo model. - Risa Yamaoka; Fumito Kanada; Masaya Nagaya; Masaru Takashima; Yoshihiro Takamura; Masaru Inatani; Masaya Oki (PLoS ONE, 2022)
Although cataracts affect almost all people at advanced age and carry a risk of blindness, the mechanisms of cataract development remain incompletely understood. Oxidative stress, which is a causative factor in cataract, results in DNA breakage, which suggests that DNA damage could contribute to the formation of cataracts. We developed an ex vivo experimental system to study changes in gene expression during the formation of opacities in the lens by culturing explanted rat lenses with Methylmethanesulfonate (MMS) or Bleomycin, which induce DNA damage. Lenses cultured using this experimental system developed cortical opacity, which increased in a concentration- and time-dependent manner. In addition, we compared expression profiles at the whole gene level using microarray analysis of lenses subjected to MMS or Bleomycin stress. Microarray findings in MMS-induced opacity were validated and gene expression was measured from Days 1-4 using RT-qPCR. Altered genes were classified into four groups based on the days of peak gene expression: Group 1, in which expression peaked on Day 1; Group 2, in which expression peaked on Day 2; Group 3, in which expression progressively increased from Days 1-4 or were upregulated on Day 1 and sustained through Day 4; and Group 4, in which expression level oscillated from Days 1-4. Genes involved in lipid metabolism were restricted to Group 1. DNA repair- and cell cycle-related genes were restricted to Groups 1 and 2. Genes associated with oxidative stress and drug efflux were restricted to Group 2. These findings suggest that in temporal changes of MMS-induced opacity formation, the activated pathways could occur in the following order: lipid metabolism, DNA repair and cell cycle, and oxidative stress and drug efflux.